Factors Influencing Corporate Websites’ Value - Laco, Peter; Kallová, Martina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The importance of corporate websites is indisputable. Websites allows companies to spread the information about contacts, products or services at relatively fair costs. The structure of these costs of the website creation, development and maintenance is described in our paper. The main aim of the paper is to present results of survey conducted out to describe factors that influence the value of corporate websites. This survey was realized by questionnaires for both users and companies. User point of view and corporate evaluation of website value was investigated to compare and summarize the results. The results of the survey may help companies to estimate the value of their websites and compare it with the real costs
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 275-284
Keywords: internet; website; website value; website costs; survey